ANALISIS FAKTOR RISIKO PREEKLAMPSIA PADA IBU HAMIL - Wahyuni, Maria Magdalena Dwi; Lestari, Dwi; Titisari, Ira; Fitria, Lia (Ensiklopedia of Journal, 2025)
Abstract: Throughout 2023, West Lombok Regency recorded 12,514 live births. Of these births, there were 16 mothers who died during the delivery process. The number of maternal deaths showed a significant increase compared to the previous year. The purpose of this study was to determine the risk factors for preeclampsia in pregnant women. The research design used in this study was cross sectional. The research was conducted in West Lombok Regency. The research was conducted in September 2023. The study population was all pregnant women who gave birth and were treated at Puskesmas and hospitals in West Lombok Regency. The sample amounted to 144 people. The sampling technique used Simple Random Sampling. The research instrument used a research questionnaire. Data analysis was performed univariate and bivariate. The results showed there was an association between maternal age (p value: 0.014) and gravida status (p value: 0.001) with the incidence of preeclampsia. It is recommended for pregnant women and families to consult and routinely conduct antenatal care examinations at health facilities to determine the development of maternal and fetal health and to detect complications in pregnancy.Keywords: Gravida, Preeclampsia, Age.